Apple polyphenols require T cells to ameliorate dextran sulfate sodium-induced colitis and dampen proinflammatory cytokine expression - Skyberg, Jerod A. (Society for Leukocyte Biology, 2011)
Human IBD, including UC and Crohn's disease, is characterized by a chronic, relapsing, and remitting condition that exhibits various features of immunological inflammation and affects at least one/1000 people in Western countries. Polyphenol extracts from a variety of plants have been shown to have immunomodulatory and anti-inflammatory effects. In this study, treatment with APP was investigated to ameliorate chemically induced colitis. Oral but not peritoneal administration of APP during colitis induction significantly protected C57BL/6 mice against disease, as evidenced by the lack of weight loss, colonic inflammation, and shortening of the colon. APP administration dampened the mRNA expression of IL-1β, TNF-α, IL-6, IL-17, IL-22, CXCL9, CXCL10, CXCL11, and IFN-γ in the colons of mice with colitis. APP-mediated protection requires T cells, as protection was abated in Rag-1(−/−) or TCRα(−/−) mice but not in IL-10(−/−), IRF-1(−/−), μMT, or TCRδ(−/−) mice. Administration of APP during colitis to TCRα(−/−) mice actually enhanced proinflammatory cytokine expression, further demonstrating a requirement for TCRαβ cells in APP-mediated protection. APP treatment also inhibited CXCR3 expression by TCRαβ cells, but not B or NK cells, in the colons of mice with colitis; however, depletion of CD4(+) or CD8(+) T cells alone did not abolish APP-mediated protection. Collectively, these results show that oral administration of APP protects against experimental colitis and diminishes proinflammatory cytokine expression via T cells.